To be a ‘Biainian’: some textual and archaeological manifestations - Grekyan, Yervand (ARAMAZD: Armenian Journal of Near Eastern Studies, 2020)
Some Urartian royal inscriptions dated to the 7th century BC several times mention a group of people, calling them ‘Biainians’. The context, in which the ‘Biainians’ are figuring along with ‘foreigners’, is negative, as they appear only in the curse formulae of those inscriptions. Actually, they were considered as potential threat towards the royal power. The article discusses the role and social status of those ‘Biainians’ and the manifestations of that status in written sources and in archaeological context.